Typology in Scripture - Fairbairn, Patrick, 1805-1874 (Grand Rapids, MI Kregel, 1989)
Includes bibliographical references and indexes.
Reprint. Originally published: New York: Funk and Wagnalls, 1900
Keywords: Typology (theology).; Bible. N.T. -- relation to the Old Testament; Bible -- criticism, interpretation, etc